Apoptosis induction of essential oils from Artemisia arborescens L. in human prostate cancer cells. (1st March 2023) - Russo, Alessandra; Graziano, Adriana; Bruno, Maurizio; Cardile, Venera; Rigano, Daniela
Abstract: Ethnopharmacological relevance: Prostate cancer originates from cells inside a gland, which begin to grow out of control. In the world, prostate cancer is the most common cancer in the male population. New therapeutic strategies are needed for this tumor which still has a high mortality. A. arborescens leaves and aerial parts have various ethnopharmacological uses such as anti-spasmodic, and their decoctions were used to resolve urticaria, neuralgia and several lung diseases. Often this species has been also used to treat different inflammatory-related diseases such as cancer. Aim of the study: In a continuation of our research on essential oils from medicinal plants, we have selected, two essential oils from Artemisia arborescens L. (Compositae), an aromatic shrub widely used in traditional medicine. We evaluated their pro-apototic effect on androgen-sensitive (LNCaP) and androgen-insensitive (DU-145) human prostate cancer cells. In this study, we also evaluated the anti-Signal transducer and transcription factor 3 (STAT-3) activity of both essential oils in the human prostate cancer cell lines, and the treatment with Tumor necrosis factor (TNF)-Related Apoptosis (TRAIL). Materials and methods: The cells were exposed to essential oils for 72 h and cell viability and cell membrane integrity were evaluated. Genomic DNA and the activity of caspase-3 was tested to confirm the cell death for apoptosis. Western blot analysis was employed to evaluate the expression of Bcl-2, Bax, cleaved caspase-3, cleaved caspase-9, Hsp70, STAT-3 and SOD proteins. Assays to evaluate reactive oxygen species (ROS) and GSH levels were also performed. Results: The results showed the capacity of two essential oils to activate an apoptotic process increasing the inhibition of Hsp70 and STAT-3 protein expression. In addition, our natural products sensitize LNCaP cells to Tumor necrosis factor (TNF)-Related Apoptosis (TRAIL)-induced apoptosis. Conclusions: In summary, our study provides a further contribution to the hypothesis of the use of essential oils, from traditional medicinal plants, for the treatment of tumors, and suggests that the combination of our samples with other anti-prostate cancer therapies could be used to affect prostate cancer. Graphical abstract: Image 1 Highlights: Essential oils from Artemisia arborescens L. induce apoptosis in prostate cancer cells. Essential oils from Artemisia arborescens L. sensitize LNCaP cells to TRAIL-induced apoptosis. Essential oils from Artemisia arborescens L. could avoid cell chemoresistance in prostate cancer.